Effects of Ultrasonic Waves During Waterflooding for Enhanced Oil Recovery - Dollah, Aqilah; Zainol Rashid, Zakirah; Hidayati Othman, Nur; Nurliyana Che Mohamed Hussein, Siti; Mat Yusuf, Suriatie; Shuhadah Japperi, Nur (International Journal of Engineering and Technology, 2018)
Ultrasonic waves is an unconventional enhanced oil recovery (EOR) technology and has been a point of interest as it is more economical and environmentally friendly. Numerous research works on ultrasonic waves application in EOR have been reported, nevertheless the studies on the effect of ultrasonic waves towards oil mobilization in porous media are still debatable. Therefore, this study aims to investigate the effect of ultrasonic waves on enhanced oil recovery of three types of oil (kerosene, engine oil and crude oil) and a brine sample at different temperatures (27°C, 35°C, 45°C, 55°C). A series of ultrasonic waterflooding experiments were conducted under controlled temperature conditions. Results demonstrated that oil recovery increases as the temperature increases during ultrasonic exposure compared to conventional waterflooding. The ultrasonic waves creates energy that increase the mobility of a displacing fluid thus reduce the viscosity of displaced fluids whereas the vibration energy produced from ultrasonic waves induced the mobility of the entrapped oil within the pores. The IR Spectra test indicates that the oil produced from ultrasonic simulated waterflooding for oils with different viscosity and density from the IR Spectra result without ultrasonic exposure due to the influence of flow behavior and sweep efficiencies of fluids. As conclusion, the ultrasonic cavitation is one of mechanism that could improve oil mobilization and enhanced oil recovery.